Platelet Function Testing: A Role for Personalised Therapy in Coronary Disease - Farag, Mohamed; Gorog, Diana A (Current Pharmaceutical Design, 2017)
Whilst there exist general guidelines regarding administration of antiplatelet therapy to prevent thrombotic events in patients with cardiovascular disease, the optimal therapy for a particular individuals in particular settings remains unclear. For patients with acute coronary syndrome (ACS) or those undergoing percutaneous coronary intervention (PCI), the use of potent antiplatelet agent combinations is recommended. However, some patients continue to have thrombotic events or experience bleeding events, which have been linked to the widely known variability in individual response to antiplatelet therapy, particularly to clopidogrel. Platelet function tests (PFTs) have been used in an attempt to predict ongoing thrombotic risk and to monitor the response to antiplatelet drugs. Although the cause of both thrombotic and bleeding events is multifactorial in origin, the observation that enhanced platelet reactivity is associated with recurrent thrombosis and reduced platelet reactivity with bleeding has raised hopes of identifying those at risk through the use of PFTs. Consequently, there was initial enthusiasm for the use of PFTs to guide individualized antiplatelet therapy. Few studies have been conducted, but the alteration of treatment based on the results of PFTs has not been shown to influence outcomes. Inherent limitations of the studies utilizing PFTs may indeed have contributed to the failure of this approach. Further, there are important limitations to the relevance of currently available PFTs to the in vivo situation. Refinement of existing techniques to allow the use of native blood, high shear, use of a global stimulus instead of individual agonists, assessment of thrombin generation by activated platelets, and assessment of fibrinolytic potential, should be considered to make these tests more physiological. Perhaps the results of PFTs need to be considered in combination with other prognostic factors in a more complex prediction model. The present manuscript provides an overview on the role of and value of available PFTs in contemporary clinical practice, with particular focus on possible individualized antiplatelet regimens in high risk patients.
Keywords: bleeding